2010
DOI: 10.1007/s11916-010-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Cluster Headache

Abstract: Cluster headache (CH) is a rare, excruciating primary headache disorder. A genetic basis has been suggested by family and twin studies, but the mode of transmission seems to vary and the amount of heritability is unclear. The number of genetic association studies investigating variants implicated in the pathophysiology of CH is limited. The HCRTR2 1246G > A and the ADH4 925A > G polymorphisms have been associated with CH. The former has been confirmed and may affect the hypothalamic hypocretin system. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The characteristic circadian and circannual periodicity of CH attacks and accompanying autonomic symptoms implicate the involvement of the hypothalamus in the disorder (1,8 9…”
Section: Pathophysiologymentioning
confidence: 99%
“…The characteristic circadian and circannual periodicity of CH attacks and accompanying autonomic symptoms implicate the involvement of the hypothalamus in the disorder (1,8 9…”
Section: Pathophysiologymentioning
confidence: 99%
“…The etiology and pathogenic mechanism of cluster headache has been not clarified absolutely, however, recent research has shown that genetic and environmental factors have potential relations with CH [ 3 ]. Currently, about 5%-20% of CH patients had CH family history.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the trigeminovascular system and possibly associated inflammatory processes have been implicated in causing and aggravating the pain101112. Although family members of cluster headache patients seem to be at increased risk of developing cluster headache3, indicating contribution of genetic factors, genetic studies into cluster headache have been largely unsuccessful1314. Some studies suggested involvement of the HCRTR2 gene that encodes the hypocretin type 2 receptor, but this finding could not be confirmed in other studies15.…”
mentioning
confidence: 99%